The Southern Iloilo-Hinigaran batel trade and its effects on the later, 1930-1973. - Santarita, Joefe B.
This is a descriptive study of a specific instance of inter-island trade operations between Southern Iloilo-Hinigaran from 1930-1973. The study attemps to trace the origin and development of the batel trade between Guimbal, San Joaquin and Miagao in Southern Iloilo and Hinigaran in the Southern part of Negros Occidental. It also documents the nature of the particiaption and responses of the Ilonggos and Hinigaranons and the factors that led to the demise of the trade. Likewise, it analyzes the effects of the trade on the socio-economic, political and cultural lives of the Hinigaranons., Prior to the batel operations at these points, there had been ongoing trade relations within the region. Inter-island contacts were made possible by land sea, or air. The availability of the boats had made the contacts easier and manageable. Thus, the services of the batel and other wind-motor-driven vessels were utilized to ferry people and products from one point to the other. In the Southern Iloilo-Hinigaran batel trade experience, Guimbal, had "M/V Paz III" owned by Celso Geonanga that operated from 1930 to 1967. Judge Esteban Siva's "M/V Sto Nino", on the other hand, had its operation between the towns of San Joaquin and Hinigaran from 1940 until its demise in 1965. Moreover, Daniel Saquian of Miagao acquired "M/S Jesus" in 1945 that operated only for a year. This was followed by "M/V Roberto and San Jose" that operated from 1945 to 1973. The aforementioned vessels were mostly run by de layag (sails) although some were both de layag de motor. They were approximately 35 to 49 feet long, 6 to 14 feet wide, 4 to 10 feet deep and could carry around 30 to 100 passengers per trip. The batel trade operations facilitated the expansion of trade and commercial activities in Hinigaran which led to the promotion of business opportunities for migrant sacada and harvesters. The coming of these people and their permament settlement in the town was one of the reasons which caused the expasion of local bureaucracy. The trade also led to the increase in the Hinigaran population, expansion of socio-cultural services, continuance of the patadyong weaving heritage, sayao and other practices, influences of the kinaray-a language as well as innovation on the local farming methods. In effect, the batel trade operation contributed a significant share to the socio-economic, political and cultural development of Hinigaran.